The Impact of Water Discharge from Tourism Sites on Water Quality: Case Study of Koh Lanta Yai, Krabi Province - Obpat , Siraphob; Worachananant, Pasinee (Burapha Science Journal, 2026)
Marine tourism is one of the activities that are important to the economy of Thailand. Koh Lanta, Krabi province is one of the marine attractions that are becoming popular with tourists. In which the consequences are increasing the amount of solid waste and water discharge from consumption of touristic activities. The release of effluent plume into the sea, which may affect the environment. In this study, water samples were collected from 5 stations as Saladan community, Klong-Daw beach, Pra-Ae beach, Klong-Nin beach, and Bakantieng beach, which found the discharge of wastewater into the water bodies. By collecting samples from canals on the banks and in the sea at the distance of 5, 10 and 15 meters from high tide level, respectively, during the low and peak of tourist season in 2017 – 2018 to study physical, chemical, and biological water quality. The study found that the discharge of wastewater from tourist sites into the sea does not affect the quality of the seawater in physical and chemical parameters but affect the biological parameter as total coliform bacteria at Saladan community exceeded the standard level. However, the amount of dissolved oxygen, phosphate-phosphorus and ammonia-nitrogen should be a parameter to be monitored because it exceeds the standards level at polluting sites and on the beach that connect to the sea. But when it flows into the sea, it still does not exceed the standard level because it was diluted by seawater. In which, if there is an additional discharge of effluent in the future, it could have an impact on the water quality of the coastal area especially stations Saladan communities, Klong Dao beach and Ba Kan Tiang beach.